Colorectal Cancer‐Derived Small Extracellular Vesicles Promote Tumor Immune Evasion by Upregulating PD‐L1 Expression in Tumor‐Associated Macrophages - Yin, Yuan; Liu, Bingxin; Cao, Yulin; Yao, Surui; Liu, Yuhang; Jin, Guoying; Qin, Yan; Chen, Ying; Cui, Kaisa; Zhou, Leyuan; Bian, Zehua; Fei, Bojian; et al. (Advanced science, 2022)
Tumor‐associated macrophages (TAMs) are one of the most abundant cell types in colorectal cancer (CRC) tumor microenvironment (TME). Recent studies observed complicated “cross‐talks” between cancer cells and macrophages in TME. However, the underlying mechanisms are still poorly elucidated. Here, PD‐L1 levels are very low in CRC cells but highly abundant in TAMs, and a specific PD‐L1+CD206+ macrophage subpopulation are identified, which is induced by tumor cells and associated with a poor prognosis. Mechanistic investigations reveal that CRC cells can secrete small extracellular vesicles (sEVs) taken up by macrophages that induce M2 like polarization and PD‐L1 expression, resulting in increased PD‐L1+CD206+ macrophage abundance and decreased T cell activity in CRC TME. sEV‐derived miR‐21‐5p and miR‐200a are identified as key signaling molecules mediating the regulatory effects of CRC on macrophages. Further studies reveal that CRC‐derived miR‐21‐5p and miR‐200a synergistically induces macrophage M2 like polarization and PD‐L1 expression by regulating the PTEN/AKT and SCOS1/STAT1 pathways, resulting in decreased CD8+ T cell activity and increased tumor growth. This study suggests that inhibiting the secretion of specific sEV‐miRNAs from CRC and targeting PD‐L1 in TAMs may serve as novel methods for CRC treatment as well as a sensitization method for anti‐PD‐L1 therapy in CRC. A specific PD‐L1+CD206+ macrophage risk subgroup is identified in colorectal cancer, which is induced by tumor‐derived sEV‐miRNAs. This subgroup promotes tumor growth by inducing an immunosuppressive tumor microenvironment. Hence, targeting specific tumor sEV‐miRNAs that regulate PD‐L1 in tumor‐associated macrophages may serve as a novel treatment strategy and a sensitization method for anti‐PD‐L1 therapy in colorectal cancer.